Transtorno de estresse pós-traumático em bancários vítimas de ataques a bancos : reações pós-traumáticas e terapia de exposição virtual - Barbosa, Márcio Englert (2018)
Post-Traumatic Stress Disorder (PTSD) is a disorder characterized by the presence of intrusion, avoidance, negative cognition and mood, and arousal symptoms after an exposure to a traumatic event. Cognitive-Behavioral Therapy (CBT) is one of the most effective therapeutic approaches for PTSD. Although effective, some patients are refractory to imaginal exposure, a frequently used thecnique in CBT for PTSD, and there is a high dropout rate. In order to increase therapeutic efficacity and treatment adherence, Virtual Reality (VR) devices have been developed since 1990 to be used in Virtual Exposure Therapy (VET). This therapy is a variation of CBT therapeutic interventions that have been showing good outcomes. However, most researches in this area study military populations or victims of terrorist attacks. Few studies have been found in literature review about the treatment of victims of urban violence, a very common type of trauma in developing countries such as Brazil. Still, some occupations are more exposed to violence, as is the case of bank employees. The objective of this study is to evaluate posttraumatic reactions in victims of bank robberies and the efficacy of VET in the treatment of PTSD. This study is composed of (1) an introduction to the main concepts used to develop this research; (2) a theoretical review of the advantages and disadvantages of VET in the treatment of PTSD; (3) an empirical section on an assessment of posttraumatic reactions on bank employees victims of bank robberies who sought psychological care; (3) a presentation of a VET protocol for victims of bank robberies who develop PTSD; (4) an evaluation of the proposed treatment protocol through a case study of a bank employee with PTSD and (5) final considerations of the main findings of this work. The results suggest that bank employee’s victims of robberies who sought psychological care present an elevated percentage of psychiatric disorders. Among them, PTSD is the most frequent. In the case study performed, the VET protocol proved to be efficient, with reduction of posttraumatic, depressive and anxiety symptoms.